10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Oral pre-exposure prophylaxis (PrEP) is an effective human immunodeficiency virus (HIV) biomedical intervention. However, men who have sex with men (MSM) continue to experience disproportionately high HIV prevalence due to intersecting marginalised identities and systemic inequities. Existing literature has identified several factors but rarely integrates multilevel and intersectional perspectives. This scoping review aimed to map existing evidence on factors influencing oral PrEP uptake and adherence among MSM globally, with a focus on how intersecting identities influence these factors. This review included studies published and conducted between 2015 and 2025. The search strategy was implemented across four electronic databases: MEDLINE (via PubMed), CINAHL (via EBSCO), Scopus, and ProQuest Dissertations and Theses. Eligible studies were analysed using the Social-Ecological Model and the Intersectionality Framework to synthesise multilevel influences on PrEP uptake and adherence. Thirteen studies were eligible and included in the review. Findings of the study identified several barriers, including low perceived HIV risk, stigma, mistrust of health care systems, limited provider engagement, and financial limitations. Facilitators included risk awareness, perceived benefits of PrEP, supportive providers, and affirming community environments. Intersecting influences such as ethnicity, religion, relationship status, and socioeconomic status also shaped PrEP engagement. Findings highlight the need for multilevel and intersectional strategies to address stigma, strengthen provider capacity, and enhance culturally affirming health care to promote equitable HIV prevention among MSM.